Toxoplasma gondii antibodies and related risk factors in mammals at Sorocaba zoo, São Paulo, Brazil - Marujo, Renata Bezerra [UNESP]; Langoni, Helio [UNESP]; Ullmann, Leila Sabrina [UNESP]; Pellizzaro, Maysa [UNESP]; Dias Neto, Ramiro Das Neves; Camossi, Lucilene Granuzzio [UNESP]; Teixeira, Rodrigo Friciello; Nunes, Adauto Veloso; Da Silva, Rodrigo Costa [UNESP]; Menozzi, Benedito Donizete [UNESP] (My University, 2017)
Toxoplasmosis is a parasitic zoonosis with worldwide distribution and different wild species either are involved in maintenance of the pathogen in the environment as definitive or intermediate hosts serving as font of feeding or prey to definitive hosts. The present study aimed to investigate Toxoplasma gondii antibodies and the risk factors relating to infection in mammals at Sorocaba Zoo, state of São Paulo, Brazil. Serum samples collected from 153 animals were analyzed using the modified agglutination test (MAT; cutoff ≥ 25). Seropositivity was found in 62 animals (40.5%; 95% CI: 33.1-48.5%), with different titers. Significant differences were observed in relation to the ages of the animals, origin, presence of free-ranging animals in the enclosure and feeding habits, through univariate analysis (p ≤ 0.05). Multivariate logistic regression analysis showed that only age (p = 0.03) had significance for the study. Adult animals were 3.5 more likely to become infected than were young ones. In relation to feeding habits, herbivores (80%) and carnivores (46.5%) were the animals most affected. These results highlight the presence of T. gondii in animals at Brazilian zoos, and suggest that continuous transmission is occurring at zoos.
Keywords: Epidemiology; Toxoplasmosis; Wild animals; Zoo